Mechanistic study of nanoparticles–surfactant foam flow in etched glass micro-models. Issue 5 (4th May 2018) - Yekeen, Nurudeen; Manan, Muhammad A.; Idris, Ahmad Kamal; Samin, Ali Mohamed; Risal, Abdul Rahim
ABSTRACT: This study was conducted in order to identify the pore-level mechanisms controlling the nanoparticles–surfactant foams flow process and residual oil mobilization in etched glass micro-models. The dominant mechanism of foam propagation and residual oil mobilization in water-wet system was identified as lamellae division and emulsification of oil, respectively. There was inter-bubble trapping of oil and water, lamellae detaching and collapsing of SDS-foam in the presence of oil in water-wet system and in oil-wet system. The dominant mechanisms of nanoparticles–surfactant foam flow and residual oil mobilization in oil-wet system were the generation of pore spanning continuous gas foam. The identified mechanisms were independent of pore geometry. The SiO2 -SDS and Al2 O3 -SDS foams propagate successfully in water-wet and oil-wet systems; foam coalescence was prevented during film stretching due to the adsorption and accumulation of the nanoparticles at the gas–liquid interface of the foam, which increased the films' interfacial viscoelasticity. GRAPHICAL ABSTRACT: